Green Bonds And Systemic Risk: Empirical Evidence From Global Markets With A Focus On Emerging Economies - Sudirman; Asyraf Mustamin; Nasira Asri; Ahmad Zaki Yamani (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study investigates whether the issuance of green bonds contributes to financial stability by mitigating systemic risk in global markets, with a particular focus on emerging economies. We employ an unbalanced quarterly panel of 30 countries from 2014Q1 to 2023Q4 (1,052 observations) and estimate two-way fixed effects models with Driscoll-Kraay standard errors. Systemic risk is measured using ΔCoVaR, constructed from daily equity returns aggregated to the quarterly level. The results indicate that higher green bond issuance, as measured by log (1 + GB/GDP), is significantly associated with lower systemic risk (β = −0.032, p < 0.01). Market volatility exacerbates systemic fragility (β = 0.047, p < 0.01), while more liquid market conditions reduce it (β = −0.018, p < 0.05). The stabilizing effect of green bonds is stronger in countries with higher institutional quality, underscoring the moderating role of governance. Overall, the preferred specifications achieve a within-R² of approximately 0.42, indicating moderate but consistent explanatory power. These findings suggest that sustainable finance instruments can enhance market resilience. Policy implications include integrating green bonds into macroprudential frameworks, improving secondary market liquidity, and harmonizing green finance taxonomies to strengthen both credibility and stability